Perencanaan Penggunaan Electrical Submersible Pump Pada Sumur “AM” - Anastasyah Maulidiah; Engeline Malrin; Mirza; Yudiaryono; Esterina Natalia Paindan; Agista Ayu Ramadhani; Pratama Bagus Restu.S (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2022)
"AM" wells are wells that no longer have the ability to produce fluid on their own. So it requires the utilization of artificial lift. The artificial lift process it self aims to increase fluid pressure so that it can flow to the surface. The production process for this well has been carried out by natural flow with a production of 593 BFPD. After several years of production, the reservoir pressure will decrease and the ability to lift the fluid will also decrease. If the pressure drop experienced by the reservoir is very large, the reservoir can no longer produce oil to the surface. But referring to the capability of the well, the production of this well can still be increased by using an Electric Submersible Pump (ESP) type artificial lift. Based on the desin method carried out is to plan the design of the artificial lift Electric SubmersibIe Pump (ESP) using manual calculations.